The Importance of Game Technologies in the Training of Future Vocational Teachers on the Basis of Competent Approach - Tukhtaeva, Zebo Sharipovna (International Journal of Psychosocial Rehabilitation, 2020)
The article explains the role and place of game technology in the training of future teachers of higher education in higher education institutions on the basis of a competent approach. In relation to traditional forms of education in higher education institutions, educational games are based on the fact that they stimulate students’ research activities and stimulate their desire to supplement their knowledge in their chosen profession and related fields. The most important functions of games are highlighted. In the learning process, the advantages of combining game technology with other technologies and teaching based on game technology from other teaching methods are highlighted.